Mechanism and optimal design of self-separating multilayer composite triboelectric nanogenerators - Jie Zhang; Jueliang Liu; Yizhou Zuo; Jin Huang; Chengyan Du; Hao Wang; Pengbing Zhao; Yupeng Yang; Yiqun Zhang; Lei Yin; Jianjun Wang; Shan Jiang (Materials & Design)
Triboelectric nanogenerators (TENGs) utilize the triboelectric effect to convert low-frequency, distributed, and irregular mechanical energy from the environment into electrical energy, finding applications in environmental monitoring, biomedicine, wearable electronics, and other fields. In single-layer vertical contact-separation mode TENGs, the output power is often limited by the friction contact area. In contrast, multilayer stacked TENGs require additional driving forces for separation motion. To achieve enhanced power output, we designed a multilayer composite self-separating TENG featuring a flexible hemispherical self-separating structure that leverages the hyperelastic properties of polydimethylsiloxane (PDMS). An electric field theoretical model was developed for the spherical structure of the triboelectric dielectric layer to elucidate its power generation mechanism. Sensitivity analysis, combining structural parameters and external mechanical excitation simulations, was conducted to optimize the output performance of the multilayer composite TENG. Finally, comparative experiments demonstrated that the multilayer composite design increased output power density by 3.9 times compared to a single-layer parallel-plate TENG.